Can Fraction of Inspired Oxygen Predict Extubation Failure in Preterm Infants? - Eugenio Spaggiari; Maria Amato; Ornella Angela Ricca; Luigi Corradini Zini; Ilaria Bianchedi; Licia Lugli; Alessandra Boncompagni; Isotta Guidotti; Cecilia Rossi; Luca Bedetti; Lorenzo Iughetti; Alberto Berardi (Children, 2022)
Background: Prolonged mechanical ventilation in preterm infants may cause complications. We aimed to analyze the variables affecting extubation outcomes in preterm infants at high risk of extubation failure. Methods: This was a single-center, observational, retrospective study. Extubation failure was defined as survival with the need for reintubation within 72 h. Successfully extubated neonates (group 1) were compared to those with failed extubation (group 2). Multivariate logistic regression analysis evaluated factors that predicted extubation outcomes. Results: Eighty infants with a birth weight under 1000 g and/or gestational age (GA) under 28 weeks were included. Extubation failure occurred in 29 (36.2%) and success in 51 (63.8%) neonates. Most failures (75.9%) occurred within 24 h. Pre-extubation inspired oxygen fraction (FiO2) of 27% had a sensitivity of 58.6% and specificity of 64.7% for extubation failure. Post-extubation FiO2 of 32% had a sensitivity of 65.5% and specificity of 62.8% for failure. Prolonged membrane rupture (PROM) and high GA were associated with extubation success in multivariate logistic regression analysis. Conclusions: High GA and PROM were associated with extubation success. Pre- and post-extubation FiO2 values were not significantly predictive of extubation failure. Further studies should evaluate if overall assessment, including ventilatory parameters and clinical factors, can predict extubation success in neonates.